Joint Interference mitigation with channel estimated in Underwater Acoustic OFDM system - Huang Mei; Sun Haixin; Cheng En; Kuai Xiaoyan; Xu Xiaoka (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Multicarrier modulation in the form of orthogonal frequency-division-multiplexing (OFDM) has been actively pursued in underwater acoustic communications. However, carrier frequency offset (CFO) can cause significant performance degradation in OFDM systems. Although underwater acoustic communication was recently the focus of research, literatures about joint interference mitigation with channel estimation using compressed sensing (CS) has been very limited in underwater acoustic OFDM. In the Cyclic prefix orthogonal frequency division multiplexing (CP-OFDM) system, a novel method was proposed which combined interference mitigation with channel estimation based on compressed sensing (CS).The novel joint optimization model combined CFO estimation with CS-based channel estimation based on the sparse in the delay-Doppler domain by using the null sub-carriers. Simulations and tank experiments have verified the performance of the receiver based on the joint interference mitigation and CS channel estimation. This method enables the OFDM system is effective against the CFO, and has better robustness. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.2883